Export performance and trade competitiveness of the Malaysian cocoa products - Idris, Nurjihan; Abdel Hameed, Amna Awad; Niti, Mohd Azaly; Mohamed Arshad, Fatimah (Academic Journals, 2011)
Malaysia cocoa beans have decreasing trend, on the other hand, export of cocoa products such as cocoa butter, cocoa powder and cocoa paste has increased significantly over the years, as Malaysia becomes one of the largest cocoa grinders in the world. However, continuous increase in price of cocoa may affect the Malaysian grinders industry since raw materials have become more expensive. Hence, Malaysia may have to think again on the decision of producing cocoa beans or cocoa products. The second question that needs to be addressed is: Does Malaysia has advantage to compete with other major exporting countries in cocoa beans or products? Thus, this study aims to investigate the competitiveness of Malaysia as compared to other major exporters of cocoa beans and cocoa products. Two instruments are used, that is, relative export advantage index (RXA) and constant-market-share (CMS). RXA measures comparative advantage for these products. CMS technique examines changes in Malaysia export position based on three separate effects, namely; size-of-market, distribution and competitiveness. RXA indicates that through 1991 to 2005, Malaysia has comparative advantage in cocoa butter and cocoa powder. The CMS analysis suggests positive total export gain for both commodities which is derived from competitive effect and size of market effect.